Pengaruh Sop, Gaji, Dan Insentif Terhadap Kinerja Pendidik Di Lembaga Kursus Peace Pare - Mohammad Said; Umi Nadhiroh; Erwin Syahputra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the effect of SOPs, Salaries, and Incentives on the performance of educators at the PEACE Pare Course Institute. The method used is quantitative. The population in this study was all 30 educators of the PEACE Pare Course Institute. The analytical tools used in this study are validity and reliability tests, classical assumption tests, multiple linear regression tests, F tests and t tests, determinant coefficients. Data processing using SPSS 23 statistics for windows. Based on the results of the study, it is known that simultaneously SOPs, Salaries, and Incentives have a significant and positive effect on educator performance. The results of the Incentive Variable analysis are the most dominant influence on performance where the coefficient value is 0.895 compared to the SOP and Salary variables whose coefficient values are only -0.244 and 1.926. This does not fit with the initial hypothesis